Qu’est-ce que la gestion des risques dans les contrats internationaux ? - Perret, Louis (Assurances)

(untitled) (HEC Montréal, 1990)
ln his article, Mr. Louis Perret first explains the concept and method of risk management, and then applies it to international contracts. This management technique consists of obtaining an overall grasp of all the stages of an operation before deciding to undertake it. One must therefore pinpoint and assess the importance of the various risks which may prevent the operation from progressing smoothly. Only with such facts in hand can a manager decide whether or not to go ahead with a project. If he decides to pursue an operation, he must take various steps to avoid, prevent and minimize risks, notably through contractual clauses. He must then obtain the best financing for the now reduced risks either by assuming them himself or by transferring them to a private or government insurer. The market approach, which is based on calculated and assumed risks, should foster the international development of companies and help them expand their horizons, particularly in developing nations.